Parameterised drag model for the underlying surface roughness of buildings in urban wind environment simulation. (1st February 2022) - Fan, M.Y.; Li, W.J.; Luo, X.L.; Shui, Q.X.; Jing, L.Z.; Gu, Z.L.; Yu, C.W.
Abstract: Knowledge of the flow field in the urban canopy layer (UCL) is of great significance in guiding the layout of buildings in blocks and mitigating local air pollution. Large eddy simulation (LES) with relatively high precision can simulate the flow field in the UCL. Considering the limitations of computational power, building resistance source parameterisation is an effective method of solving the average blocking effect of buildings on airflow and reducing the number of grids. Belcher's drag model has been widely used for calculating the average flow field in the UCL. However, the model does not consider the influence of the horizontal recirculation region and the variation of the canopy-drag length scale in the height direction. Therefore, a parameterised drag model for the resistance source of building(s) was improved by considering the horizontal recirculation region and effective roughness density. The simulation results suggest that the horizontal recirculation area of an isolated building is mainly affected by the spanwise width of the building at a certain height and presents a quadratic function distribution in the height direction, with a maximum at approximately z/H = 0.45. The validation of the isolated building and building arrays with different layouts demonstrated that the parameterised drag model could reveal the average flow field more accurately than Belcher's drag model. Highlights: The average sectional drag coefficient is key point to build parameterized drag model. Must to consider recirculation region calculating average sectional drag coefficient. Horizontal recirculation area of isolated building present a quadratic function distribution in the height direction.